PENGARUH LEVERAGE TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN SUB SEKTOR ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Natalia, Delita; Suherman, Acep (Universitas Nusantara PGRI Kediri, 2020)
This study aims to determine the effect of asset growth and leverage on dividend policy. Asset growth, leverage and dividend policy are used as variables in the study. This research uses quantitative method with an associative approach. The population in this study is the financial reports of sub sektor cigarette manufacturing companies 2016-2018 of three cigarette companies and 36 financial reports are used as the sample. In this study sampling technique. Data collection techniques by documenting secondary data. The data analysis technique used is the classic assumption and regression tests. The result of this study indicates: the independent variable is leverage while the dependent variable is dividend policy. The results of this study indicate that partially Leverage variables have no effect on dividend policy.